Surface mechanics of a stretched elastomer layer bonded on a rigid substrate. (September 2020) - Song, Zhaoqiang; Liang, Xiaodong; Li, Kai; Cai, Shengqiang
Abstract: Thin elastomer layers bonded on a rigid substrate can be found in diverse engineering applications, in which the elastomers are often in stressed state. Previous studies have shown abundant evidence that the prestresses in an elastomer layer can greatly influence its mechanical behaviors. In this article, we have analytically derived the surface Green's function of a stressed elastomer layer with finite thickness and bonded on a rigid substrate, which enables us and others to compute surface deformation of the elastomer layer subjected to any arbitrary surface force. By using the derived surface Green's function, we further study the indentation of a prestressed elastomer layer, as well as the deposition of a liquid droplet and adhesion of a cell on a prestressed elastomer layer. The effects of prestresses and finite thickness of the elastomer layer on those problems have been uncovered.